Control of Autonomous Robot Arm - Basu, Rahul (Journal of Science and Technology, 2024)
This paper explores the use of AI and ML technologies in space exploration, focusing on controlling robotic arms like the Puma robot arm using feedback technology. It discusses the application of Kalman Filters to a Robot arm augmented by real time feedback. The paper also highlights the OWI arm in the field of robotics and its potential impact on space exploration. The study underscores the potential of AI/ML technologies in space exploration and the role of low cost experiments in driving these advancements.